2014
DOI: 10.1002/ijc.28640
|View full text |Cite
|
Sign up to set email alerts
|

Is HPV DNA testing specificity comparable to that of cytological testing in primary cervical cancer screening? Results of a meta‐analysis of randomized controlled trials

Abstract: Human-papillomavirus (HPV) DNA testing has been proposed as an alternative to primary cervical cancer screening using cytological testing. Review of the evidence shows that available data are conflicting for some aspects. The overall goal of the study is to update the performance of HPV DNA as stand-alone testing in primary cervical cancer screening, focusing particularly on the aspects related to the specificity profile of the HPV DNA testing in respect to cytology. We performed a metaanalysis of randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 52 publications
(183 reference statements)
3
25
0
4
Order By: Relevance
“…Nevertheless, the transient nature of age-dependent prevalence of HPV infection suggests that the overall specificity and/or positive predictive value can be compromised [12][13][14]. Only a minute fraction of HPV infections actually progress to cervical neoplasia.…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, the transient nature of age-dependent prevalence of HPV infection suggests that the overall specificity and/or positive predictive value can be compromised [12][13][14]. Only a minute fraction of HPV infections actually progress to cervical neoplasia.…”
Section: Introductionmentioning
confidence: 95%
“…HPV DNA testing has proven to be an important adjunct to cervical cytology (Pap) screening for the early detection of precancerous lesions [3]. Recent studies have demonstrated that HPV DNA testing has higher sensitivity than Pap smear testing [4,5]. In March 2014, the U.S. Food and Drug Administration advisory panel recommended that HPV DNA testing could serve as the primary tool for cervical cancer screening.…”
Section: Introductionmentioning
confidence: 99%
“…Estas técnicas tienen la ventaja de una mayor sensibilidad que el tamizaje convencional pero una menor especificidad debido a que pesquisan infecciones no persistentes o persistentes no progresivas, además de las infecciones asociadas a neoplasias intra-epiteliales [10][11][12]26 .…”
Section: Otros Problemasunclassified
“…Meta-análisis comparativos entre el diagnóstico de infección por VPH usando métodos moleculares versus citología convencional indican que en mujeres > 30 años, estos nuevos métodos permitirían detectar un mayor número de casos de NIE tipo II y III con la misma especificidad que la citología y podrían ser justificados en este segmento 10 . Sin embargo, hasta ahora estas nuevas metodologías se han aplicado y evaluado principalmente en países desarrollados y su costo es mayor que el del Papanicolau.…”
Section: Otros Problemasunclassified
See 1 more Smart Citation